Goodbye Sékou : Perdre un esprit engagé dans les politiques de développement et la recherche en santé globale - Thiongane, Oumy (Anthropologica, 2024)
While paying tribute to Sékou, one of the important collaborators of Global Vaccine Logics who left us in December 2020, we want to highlight the important place that research assistants and young African researchers play in global health projects. Part of Sékou’s trajectory, while revealing beyond the reflections, the intertwining of health, extraction, and commitment, leads us to make a vibrant call to improve the conditions of research in African universities and to favor the decolonization of the conditions of knowledge production in order to pave the way, to leave room and to give voice and credit to the expertise of the young African generation that is taking over.